What Is the Radiation Impact of Extreme Solar Energetic Particle Events on Mars? - Jian Zhang; Jingnan Guo; Mikhail I. Dobynde (Space Weather)
Abstract Solar Energetic Particles (SEP) are one of the major sources of the Martian radiation environment. It is important to understand the SEP‐induced Martian radiation environment for future human habitats on Mars. Due to the lack of a global intrinsic magnetic field, Solar Energetic Particles (SEPs) can directly propagate through and interact with its atmosphere before reaching the surface and subsurface of Mars. Mars has many high mountains and low‐altitude craters where the atmospheric thickness can be more than 10 times different than one another. The SEP‐induced surface radiation level may therefore be very different from one location to another. We thus consider the influence of the atmospheric depths on the Martian radiation levels including the absorbed dose, dose equivalent, and (human‐)body effective dose induced by SEPs at varying heights above and below the Martian surface. The state‐of‐the‐art Atmospheric Radiation Interaction Simulator based on GEometry And Tracking Monte‐Carlo method has been employed for simulating particle interactions with the Martian atmosphere and terrain. We find that even the thinnest Martian atmosphere reduces radiation dose from that in deep space by at least 65%, and the shielding effect increases for denser atmosphere. Furthermore, we present a method to quickly forecast the SEP‐induced radiation in different regions of Mars with different surface pressures.